ISMAIL MARZUKI: MUSIK SEBAGAI ALAT PROPAGANDA DALAM MENGHADAPI MASA MEMPERTAHANKAN KEMERDEKAN INDONESIA (1945-1950) - Samudra Eka Cipta; Pendi Kurniawan (Jurnal Humaniora & Sosial Sains, 2025)
This study discusses the struggle of Ismail Marzuki as a National Hero. Ismail Marzuki is a composer and once worked at the RRI Radio Station (Radio Republik Indonesia). When RRI was controlled by the Dutch in 1947, Ismail Marzuki left RRI and continued to struggle through the works he performed. Ismail Marzuki's works are very much remembered by the public, especially since many of the works contain stories about struggle. This article uses a historical approach in analyzing the role of Ismail Marzuki as an artist and as a national hero.